Computation of EABF and EBF for basalt rock samples - Karabul, Yasar; Susam, Lidya Amon; Icelli, Orhan; Eyecioglu, Onder (ELSEVIER SCIENCE BV, 2015)
In this study, certain photon absorption parameters including the energy absorption buildup factor (EABF) and exposure buildup factor (EBF) have been investigated for three different basalt samples collected from different parts of Van city. Radiation shielding properties of the basalt samples indicated a strong correlation between photon energy absorption parameters and values of EABF and EBF of basalt samples. It was found that EABF and EBF parameters are related to radiation shielding properties of basalt samples. A new method and algorithm based on ZXCOM was used. Instead of calculating G-P fitting parameters for every effective atomic number (Z(eff)), EABF and EBF were calculated for Z(eff) by interpolation, using ANSI/ANS 6.4.3 standard data available for Z(eff). (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Mass attenuation coefficient; Effective atomic number; Radiation shielding; Basalt; Buildup factors; EFFECTIVE ATOMIC-NUMBER; MASS ATTENUATION COEFFICIENTS; ABSORPTION BUILDUP FACTORS; COMPTON-SCATTERING; BORON-COMPOUNDS; RADIATION; CONCRETE; RAYLEIGH; ENERGY; STEEL; Instruments & Instrumentation; Nuclear Science & Technology; Physics